Targeted delivery of mitomycin C-loaded and LDL-conjugated mesoporous silica nanoparticles for inhibiting the proliferation of pterygium subconjunctival fibroblasts. (August 2020) - Wu, Mengliang; Wang, Shangfeng; Wang, Yan; Zhang, Fan; Shao, Tingting
Abstract: Pterygium is a degenerative disease that characterized by excessive fibrovascular proliferation. To reduce the recurrence rate, surgery is the main strategy, in combination with adjacent procedures or adjunctive therapy. One of the most common adjunctive agents, mitomycin C (MMC), is known as an alkylating agent that inhibits fibroblast proliferation but is limitedly applied in pterygium due to various complications. A previous study demonstrated that activated pterygium subconjunctival fibroblasts overexpressed low-density lipoprotein (LDL) receptors. In this study, we designed and synthesized MMC-loaded mesoporous silica nanoparticles conjugated with LDL (MMC@MSNs-LDL) to deliver MMC into activated pterygium fibroblasts in a targeted manner. The MMC loading efficiency was approximately 6%. The cell viability test (CCK-8 assay) revealed no cytotoxicity for the empty carrier MSNs at a concentration of ≤1 mg/ml after administration for 48 h in subconjunctival fibroblasts. Primary pterygium and normal human subconjunctival fibroblasts with or without stimulation by vascular endothelial growth factor (VEGF) were treated as follows: 1) 10 μg/ml MMC@MSNs-LDL for 24 h (MMC concentration: 0.6 μg/ml); 2) 0.2 mg/ml MMC for 5 min then cultured for 24 h after MMC removal; and 3) normal culture without any drug treatment. At 24 h, the anti-proliferative effect of MMC@MSNs-LDL in activated pterygium fibroblasts was similar to that of MMC (cell viability: 46.2 ± 5.5% vs 40.5 ± 1.1%, respectively, P = 0.349). Furthermore, the cytotoxicity of MMC@MSNs-LDL to normal fibroblasts with or without VEGF stimulation was significantly lower than that of traditional MMC (cell viability: 75.6 ± 4.4% vs 36.0 ± 1.5%, respectively, P < 0.001; 84.7 ± 5.5% vs 35.7 ± 1.3%, P < 0.001). The binding of fluorescently labeled MMC@MSNs-LDL in fibroblasts was assessed using confocal fluorescence microscopy. The uptake of targeted nanoparticles in fibroblasts was time dependent and saturated at 6 h. VEGF-activated pterygium fibroblasts showed more uptake of MMC@MSNs-LDL than normal fibroblasts with or without VEGF activation (both P < 0.001). Our data strongly suggest that MMC@MSNs-LDL had an effective antiproliferative role in activated pterygium fibroblasts, with reduced toxicity to normal fibroblasts compared to traditional application of MMC. LDL-mediated drug delivery might have great potential in the management of pterygium recurrence. Highlights: LDL is conjugated with mitomycin C-loaded nanoparticles for targeted delivery. Activated pterygium fibroblasts uptake more targeted nanoparticles. LDL-targeted MMC shows a good antiproliferative effect on pterygium fibroblasts. LDL-targeted MMC shows a lower toxicity to normal fibroblasts.